The Effects of an Ecological Diversifying Experience on Creativity: An Experimental Study - Chirico, Alice; Carrara, Sofia; Bastoni, Sofia; Gianotti, Elena; Gaggioli, Andrea (Frontiers in Psychology, 2020)
Sometimes, life houses rare and unexpected events, as moving abroad or meeting a special person unexpectedly. Recently, these situations have been indicated as “Diversifying Experiences” (DEs), defined as unusual and unexpected events that drag people outside their daily routine and accustomed schemas. The core mechanism of DEs would entail the disruption of our mental schema which can facilitate unexpected connections among even distant ideas, thus enhancing people’ cognitive flexibility, i.e., a key component of creative thinking. Despite both qualitative and lab-based studies have investigated the features of these experiences, an ecological assessment of their properties also in relation with creativity is still an open issue. The aim of this research is to study the DEs-creativity link in a more ecological way, on the basis of a real-life disruptive experience of light deprivation. Specifically, we compared an ecological DE artistic established entertainment format, i.e., “Dialogue in the Dark” in which seeing people performed several daily-life activities but in the absence of light – to an equivalent experience in which the same activities were acted in the sunlight. The absence of light played the role of violating mechanism, framed within the ecological experiential format of the “Dialogue in the Dark”. We compared visitors’ emotional profile (PANAS, ad hoc Adjective Checklist), perceived impact of the experience (Centrality of Event Scale-CES) and creative performance (Torrance Test of Creative Thinking-TTCT) in both groups of sighted people (in absence of light vs. in presence of light) and we also controlled for people’ openness to experience and need for cognitive closure, as dispositions. Results showed that (vs. control group): (i) “Dialogue in the Dark” led to worse creative performances (ii), produced more intense positive affect, (iii) resulted as a more impacting experience. Intense short-term impact of DE could have been detrimental for participants’ creativity. People may need more time to elaborate the DE and accommodate existing schema to generate more creative ideas. This is the first study proposing and succeeding in demonstrating the feasibility to investigate even real complex DEs in a controlled way, thus outlining how their link with creativity can take place in real life.